2018
DOI: 10.1016/j.psep.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation of Bisphenol A from high saline polycarbonate plant wastewater using wet air oxidation

Abstract: a b s t r a c tIn the present study, wet air oxidation (WAO) was investigated for the decomposition of bisphenol A (BPA) in high saline polycarbonate plant wastewater (PCW). The main operating conditions of the WAO process that affects the degradation efficiency, including temperature, total air pressure and reaction time were studied. The results indicate that complete BPA degradation is achieved in pH 8.5, temperature = 150 • C, total air pressure of 3 MPa and 120 min. In addition, by prolonging the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This result is explained by the fact that the aromatic structure of the phenolic compounds gives them a high activation energy for WAO. Consequently, higher reaction temperature is required to get over such high activation energy barriers (Mirzaee et al, 2018). In order to avoid excessive temperature conditions and thus reduce the cost, the use of a catalyst is necessary to improve the conversion of BPA and to avoid the formation of by-products.…”
Section: Thermal Decomposition (Blank Tests)mentioning
confidence: 99%
“…This result is explained by the fact that the aromatic structure of the phenolic compounds gives them a high activation energy for WAO. Consequently, higher reaction temperature is required to get over such high activation energy barriers (Mirzaee et al, 2018). In order to avoid excessive temperature conditions and thus reduce the cost, the use of a catalyst is necessary to improve the conversion of BPA and to avoid the formation of by-products.…”
Section: Thermal Decomposition (Blank Tests)mentioning
confidence: 99%
“…9) . It is reported that BPA degradation in AOPs technologies, such as in the CWPO process, may proceed through different mechanisms, including CO 2 elimination, dihydroxylation, cleavage of CeC bond, OH group addition and oxidation mechanism [2,55]. Fig.…”
Section: Cwpo Process On Bpa Degradation In Aqueous Solution and Its mentioning
confidence: 99%
“…Polycarbonate plant wastewater (PCW) is typically characterized by high levels of aromatic hydrocarbons and phenolic substances, such as Bisphenol A, as well as high concentrations of salinity, inorganic dissolved salts and total dissolved solids (TDS) [1][2][3]. Bisphenol A (2, 2-bis (4-hydroxyphenyl) propane, BPA), characterized by two phenolic rings joined together through isopropylidene as bridging group, is a main industrial chemical widely used in plastic industry as intermediate in the manufacturing of polycarbonate and in the production of epoxy resins and corrosion-resistant unsaturated polystyrene resins [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If mineralization is achieved during the Fenton reaction, the TOC decreases but if only partial oxidation occurs it remains constant with a decrease of the COD [52]. In addition, AOS (average oxidation state) and COS (carbon oxidation state) parameters have been evaluated for a better understanding of the degree of oxidation of a process [53][54][55].…”
Section: Introductionmentioning
confidence: 99%